Strengthening Local Retribution to Enhance Local Own Source Revenue - Olivia Sahertian; Arthur Reinaldo Tanihatu (Univiversitas Dr. Djar Wattiheluw, 2026)
Local retribution is an important source of Local own source revenue (PAD) that supports regional fiscal capacity. However, many local governments face challenges in optimizing retribution performance. This study aims to analyze the contribution, effectiveness, and growth of local retribution revenue and identify factors affecting its performance in Ambon City, Indonesia. Using a mixed methods approach, this study examines budgeted and realized retribution revenue data from 2023–2025 and qualitative evidence from interviews with three local government officials. The findings indicate that local retribution has not yet optimally supported PAD, as reflected in declining contribution and negative growth performance, while effectiveness fluctuated during the study period. The decline was influenced by weak supervision, unrealistic targets, limited revenue potential mapping, manual collection systems, insufficient digitalization, low public awareness, and inadequate infrastructure. This study highlights the importance of integrating financial analysis with institutional factors to strengthen local revenue management.